Pemberdayaan Ekonomi UMKM Berbasis Kearifan Lokal di Desa Budaya Lingga Kabupaten Karo - Intan Juwita Damanik; Putri Yuanita; Rahmawati Br Sembiring; Wan Shalah Sabila; Muhammad Ikhsan Harahap (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Lingga Cultural Village in Karo Regency has a strong potential for local wisdom, but its use in community economic development, especially Micro, Small, and Medium Enterprises (MSMEs) is still not optimal. The main problems include limitations in product packaging, branding, and marketing strategies that are able to represent Karo's cultural values. The Real Work Lecture Program (KKN) aims to empower the MSME economy based on local wisdom to increase business competitiveness. The implementation method uses the Participatory Action Research (PAR) approach involving 10 partner MSMEs engaged in culinary and traditional handicrafts. The program is implemented through three main activities, namely: 1) re-branding and packaging design workshops based on Karo's motives and philosophy; 2) digital marketing training with an emphasis on product culture storytelling; and 3) simple business management assistance. Program evaluation is carried out through observation, interviews, and comparison of conditions before and after activities. The results of the program show an increase in the capacity of MSMEs, characterized by 100% of partner MSMEs having a new visual identity, an increase in digital promotion activities from 30% to 80% of MSMEs active on social media, and the compilation of product narratives based on local culture. This program concludes that the empowerment of MSMEs that focuses on strengthening local wisdom is effective in increasing business competitiveness while contributing to the preservation of the cultural identity of the Lingga Cultural Village.